2022
DOI: 10.1186/s11658-022-00382-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of PAR signaling through receptor crosstalk

Abstract: Protease activated receptors (PARs) are among the first receptors shown to transactivate other receptors: noticeably, these interactions are not limited to members of the same family, but involve receptors as diverse as receptor kinases, prostanoid receptors, purinergic receptors and ionic channels among others. In this review, we will focus on the evidence for PAR interactions with members of their own family, as well as with other types of receptors. We will discuss recent evidence as well as what we conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 151 publications
0
4
0
Order By: Relevance
“…It has also been discovered that the T2 environment-derived cytokine response alters PAR-2 polarisation in human airway epithelial cells, therefore reducing tolerance to protease exposure and resulting in the promotion of allergic inflammation in the airway [ 157 ]. Even though it was initially suggested that G protein-coupled receptors function as solitary monomeric units, there is evidence that PARs can form dimers or can transactivate other types of receptors [ 189 ]. PAR-2 facilitates ROS signalling and has potential to transactivate receptor tyrosine kinases (RTKs) in the airways [ 190 ].…”
Section: Signalling Pathways Involved In Mediating the Allergen Serin...mentioning
confidence: 99%
“…It has also been discovered that the T2 environment-derived cytokine response alters PAR-2 polarisation in human airway epithelial cells, therefore reducing tolerance to protease exposure and resulting in the promotion of allergic inflammation in the airway [ 157 ]. Even though it was initially suggested that G protein-coupled receptors function as solitary monomeric units, there is evidence that PARs can form dimers or can transactivate other types of receptors [ 189 ]. PAR-2 facilitates ROS signalling and has potential to transactivate receptor tyrosine kinases (RTKs) in the airways [ 190 ].…”
Section: Signalling Pathways Involved In Mediating the Allergen Serin...mentioning
confidence: 99%
“…Regulatory effects mediated through PAR1 and PAR4 are determined by the ability of these receptors to form heterodimeric complexes with PAR2 and PAR3 [ 245 , 256 ]. In the case of PAR1, the formation of a heterodimeric complex with PAR2 provides PAR1-induced activation of PAR2 and stimulation of thrombin-mediated β-arrestin signaling, which significantly contributes to PAR-dependent effects on blood coagulation and inflammation [ 257 ].…”
Section: Allosteric Regulators Of Proteinase-activated Receptorsmentioning
confidence: 99%
“…A Regulatory effects mediated through PAR1 and PAR4 are determined by the ability of these receptors to form heterodimeric complexes with PAR2 and PAR3 [241,253]. In the case of PAR1, the formation of a heterodimeric complex with PAR2 provides PAR1induced activation of PAR2 and stimulation of thrombin-mediated β-arrestin signaling, which significantly contributes to PAR-dependent effects on blood coagulation and inflammation [254].…”
Section: Allosteric Regulators Of Proteinase-activated Receptorsmentioning
confidence: 99%